Epidemiology of sarcopenia in elderly Japanese - Atsumu Yuki; Fujiko Ando; Rei Otsuka; Yasumoto Matsui; Atsushi Harada; Hiroshi Shimokata (Japanese Society of Physical Fitness and Sports Medicine, 2015)
Sarcopenia, a degenerative loss of skeletal muscle mass and strength, impacts daily life among the elderly. Because few cohort studies have examined muscle mass, muscular strength, physical performance, and probable confounding factors in detail, the prevalence of sarcopenia among the elderly in Japan is unclear. In this review, we examine the prevalence of sarcopenia based on the criteria of the Asian Working Group for Sarcopenia (AWGS) using a large-scale cohort of randomly selected community-dwelling elderly in Japan. Participants included 949 elderly (479 men and 470 women) aged 65-91 years who participated in the seventh wave examination of the National Institute for Longevity Sciences - Longitudinal Study of Aging between July 2010 and July 2012. The prevalence of low muscle mass was 43.2% in men and 20.2% in women. The prevalence of low muscle strength was 10.0% in men and 21.5% in women, and the prevalence of low physical performance was 5.4% in men and 9.2% in women. The prevalence of sarcopenia based on a diagnosis of low muscle mass, low muscle strength, and low physical performance was 9.6% in men and 7.7% in women. Elderly who were diagnosed with sarcopenia included 1,320,000 men and 1,400,000 women. These data could be of great help to clinicians and healthcare professionals and contribute to the development of prevention and treatment strategies for sarcopenia in Japan.